Toward the development of a conceptual framework for the complex interaction between environmental changes and rural-urban migration - Mianabadi, Ameneh; Davary, Kamran; Mianabadi, Hojjat; Kolahi, Mahdi; Mostert, Erik (Frontiers in Water, 2023)
Environmental changes can result in dramatic increases in human migration as households become unable to adapt to such changes. Addressing environmental migration is a complex puzzle that can become a wicked problem. Despite the growing literature on the nexus between environmental change and migration, the inextricable link between nature and society has made it difficult to establish causal relations between the two. To examine the relationship between environmental change and migration, it is necessary to develop a conceptual model that includes environmental changes as potential causes of rural-urban migration (RUM). Such a model should be built on an enhanced understanding of the different factors that stimulate environmentally induced RUM. This paper proposes such a model, focusing on loss of agricultural land, loss of agricultural productivity and the economic repercussions of these losses. The model is based on the model of Perch-Nielsen et al. but extends this model by incorporating additional factors. In our model, the three leading causes of RUM are climate change, human maladaptive activities, and hydro-climatic disasters (the push factors). In addition, there may be pull factors in the cities. RUM may be counteracted or reduced by governmental policy and individuals' characteristics. The model was applied to Iran. The results show that the model can help to bridge the knowledge gap regarding environmentally induced RUM and may inform policymaking on RUM and related issues, such as environmental management and adaptation to climate change.